Urolithin A Promotes Angiogenesis and Tissue Regeneration in a Full-Thickness Cutaneous Wound Model - Feng, Zhen-hua; Chen, Jia; Yuan, Pu-tao; Ji, Zhong-yin; Tao, Si-yue; Zheng, Lin; Wei, Xiao-an; Zheng, Ze-yu; Zheng, Bing-jie; Chen, Bin; Chen, Jian; Zhao, Feng-dong (Frontiers in Pharmacology, 2022)
The rapid treatment of wounds remains a critical clinical challenge. During the wound healing process, new blood vessels are needed to deliver nutrients and oxygen to the wound area. In this study, we explored the angiogenesis ability and mechanism of Urolithin A (UA) in wound healing process. In vitro experimental results show that co-culture with UA (5-20 μM) could promote the proliferation, migration and angiogenesis abilities of human umbilical vein endothelial cells (HUVECs). Moreover, a full-thickness cutaneous wound model was used to investigate the effect of UA in vivo, and we found UA enhanced the regeneration of new blood vessels, which consistent with the in vitro results of accelerating angiogenesis. Based on the rapid vascularization of the wound site, the process of collagen matrix deposition and remodeling after UA treatment is also accelerated, which ultimately promotes effective wound healing. Mechanism studies have shown that UA promotes blood vessel formation by inhibiting the PI3K/AKT pathway. Our research provides evidence for UA to promote angiogenesis and tissue regeneration in skin wounds, especially ischemic wounds.